Land Transformation Analysis of Siliguri City using Remote Sensing and GIS techniques (International Journal of Food and Nutritional Sciences, 2022)
During past four decades, Siliguri city has attracted a large number of population due to economic hub of the entire north Bengal, which led to the rapid transformation of its LULC pattern. Therefore, this study is aimed to analyse the LULC changes during 1991 to 2021 by giving special emphasize on built up transformation. The Landsat TM, ETM and LISS IV data has been used for the LULC classification of the Siliguri city. Modified Maximum Likelihood Classifier approach has been adopted to generate the classified image. From the analysis it is found that there is a drastic change in built-up 1254.54 percent in respect to 1991. While teagarden, agriculture land and waterbody declined by -90.06, -97.17 and -88.76 percent, respectively. These changes are harmful for the ecological balance of the city surrounding. It can further impact on the city’s sustainable development